AARS2 leukoencephalopathy: A new variant of mitochondrial encephalomyopathy. Issue 4 (31st January 2019) - Tang, Yi; Qin, Qi; Xing, Yi; Guo, Dongmei; Di, Li; Jia, Jianping
Abstract: Background: Mutations in the mitochondrial alanyl‐transfer (t)RNA synthetase 2 (AARS2, OMIM:612035) have been linked to leukoencephalopathy recently. Till now, there have been 19 cases reported so far. However, the clinical and genetic characteristics of this disease are not fully understood. We reported an adult‐onset male leukoencephalopathy patient related to novel AARS2 gene mutations and reviewed all previous cases regarding the clinical and genetic features of AARS2 leukoencephalopathy. Methods: The spectrum of clinical symptoms and the genetic analysis of the presented patient were identified and investigated. Besides this case, we assessed previously reported cases with AARS2 gene mutations. Results: Here, we present a 30‐year‐old man with progressive motor deficits in the right lower limb and severe cerebellar ataxia for one year. MRI revealed extensive white matter lesions in periventricular regions and along the corticospinal tract. Genetic analysis revealed two new heterogeneous missense mutations in AARS2 : c.179C>A and c.1703_1704del. We described the ragged red fiber (RRF) for the first time, suggesting that AARS2 ‐related leukoencephalopathy be a new variant of mitochondrial encephalomyopathy. Gradual improvement in motor function was observed with intravenous coenzyme complex treatment. We also summarized our case and all previously reported cases to provide an overview of AARS2 ‐related late‐onset leukoencephalopathy. Then, we compared clinical and neuroimaging features of AARS2 ‐related leukoencephalopathy with three other frequently diagnosed types of adult‐onset leukoencephalopathy to provide insight into diagnostic strategies. Conclusion: The characteristic MRI abnormalities and clinical symptoms described here may help to distinguish AARS2 ‐related leukoencephalopathy from other adult‐onset leukoencephalopathies. The combination of encephalopathy and myopathy strongly suggest that AARS2 ‐related leukoencephalopathy is a new variant of mitochondrial encephalomyopathy. The response to coenzyme complex will shed light on future therapy investigation. Abstract : Here, we report the first description of typical ragged red fiber (RRF) identified by muscle biopsy in a male patient with AARS2 ‐related leukoencephalopathy, suggesting that AARS2 ‐related leukoencephalopathy be a new variant of mitochondrial encephalomyopathy. We summarized the main findings of our case and all previously reported 19 cases to provide an overview of the genetic, clinical, and neuroimaging characteristics of AARS2 ‐related late‐onset leukoencephalopathy. Then, we compared clinical and neuroimaging features of AARS2‐ related leukoencephalopathy with three other frequently diagnosed types of adult‐onset leukoencephalopathy to provide insight into diagnostic strategies.